Fostering Transdisciplinary Research Through Citizen Science: The Project Val d’Hérens 1950/2050 - Emmanuel Reynard; Mélanie Clivaz; Séverine Trouilloud (Mountain Research and Development, 2023)
Citizen science is considered beneficial in improving the dialogue between researchers and nonacademic stakeholders and in supporting the transformation of regions toward greater sustainability. In this article, we discuss the challenges and benefits of the citizen science project Val d'Hérens 1950/2050—Lives, Images and Practices of a Changing Territory, which involves researchers, artists, and inhabitants of a Swiss valley.